Importance of the Inverted Control in Measuring Holistic Face Processing with the Composite Effect and Part-Whole Effect - McKone, Elinor; Aimola Davies, Anne; Darke, Hayley; Crookes, Kate; Wickramariyaratne, Tushara; Zappia, Stephanie; Fiorentini, Chiara; Favelle, Simone; Broughton, Mary; Fernando, Dinusha (Frontiers in Psychology, 2013)
Holistic coding for faces is shown in several illusions that demonstrate integration of the percept across the entire face. The illusions occur upright but, crucially, not inverted. Converting the illusions into experimental tasks that measure their strength – and thus index degree of holistic coding – is often considered straightforward yet in fact relies on a hidden assumption, namely that there is no contribution to the experimental measure from secondary cognitive factors. For the composite effect, a relevant secondary factor is size of the "spotlight" of visuospatial attention. The composite task assumes this spotlight can be easily restricted to the target half (e.g., top half) of the compound face stimulus. Yet, if this assumption were not true then a large spotlight, in the absence of holistic perception, could produce a false composite effect, present even for inverted faces and contributing partially to the score for upright faces. We review evidence that various factors can influence spotlight size: race/culture (Asians often prefer a more global distribution of attention than Caucasians); sex (females can be more global); appearance of the join or gap between face halves; and location of the eyes, which typically attract attention. Results from 5 experiments then show inverted faces can sometimes produce large false composite effects, and imply that whether this happens or not depends on complex interactions between causal factors. We also report, for both identity and expression, that only top-half-face targets (containing eyes) produce valid composite measures. A sixth experiment demonstrates an example of a false inverted part-whole effect, where encoding-specificity is the secondary cognitive factor. We conclude the inverted face control should be tested in all composite and part-whole studies, and an effect for upright faces should be interpreted as a pure measure of holistic processing only when the experimental design produces no effect inverted.